2017
DOI: 10.1186/s13643-017-0533-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of genetic variants on toxicity to anti-tubercular agents: a systematic review and meta-analysis (protocol)

Abstract: BackgroundTuberculosis patients receiving anti-tuberculosis treatment may experience serious adverse drug reactions, such as hepatotoxicity. Genetic risk factors, such as polymorphisms of the NAT2, CYP2E1 and GSTM1 genes, may increase the risk of experiencing such toxicity events. Many pharmacogenetic studies have investigated the association between genetic variants and anti-tuberculosis drug-related toxicity events, and several meta-analyses have synthesised data from these studies, although conclusions from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 45 publications
0
23
0
1
Order By: Relevance
“…Genetic polymorphisms of NAT2 , CYP2E1 and the GST family are the most studied in relation to ATDH, for they may affect the metabolism and elimination of isoniazid, or are involved in oxidant-antioxidant balance in liver cells after exposure to anti-TB drugs 12 . We previously demonstrated that CYP2E1, GSTP1 and CYP2B6 were associated with susceptibility to ATDH by a meta-analysis and a case-control study 15,30,31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic polymorphisms of NAT2 , CYP2E1 and the GST family are the most studied in relation to ATDH, for they may affect the metabolism and elimination of isoniazid, or are involved in oxidant-antioxidant balance in liver cells after exposure to anti-TB drugs 12 . We previously demonstrated that CYP2E1, GSTP1 and CYP2B6 were associated with susceptibility to ATDH by a meta-analysis and a case-control study 15,30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variants in drug metabolizing enzymes such as N-acetyltransferase 2 ( NAT2 ), cytochrome P450 2E1 ( CYP2E1 ) and glutathione S-transferases ( GSTM1, GSTT1 ), have been the most widely studied in respect to ATDH susceptibility in the Chinese population 911 , as well as other populations 12 . However, these genetic biomarkers have shown poor reproducibility in some studies.…”
Section: Introductionmentioning
confidence: 99%
“…The current study forms part of a series of systematic reviews and meta-analyses evaluating the influence of different genetic variants on toxicity to anti-TB agents, the protocol for which has been published (PROSPERO registration number: CRD42017068448) (13). This review has been conducted in accordance with the PRISMA statement (14); a completed copy of the PRISMA checklist is provided in Additional file 1.…”
Section: Methodsmentioning
confidence: 99%
“…The current study forms part of a series of systematic reviews and meta-analyses evaluating the influence of different genetic variants on toxicity to anti-TB agents, the protocol for which has been published (PROSPERO registration number: CRD42017068448) [ 18 ]. This review has been conducted in accordance with the PRISMA statement [ 19 ]; a completed copy of the PRISMA checklist is provided in Additional file 1 .…”
Section: Methodsmentioning
confidence: 99%